The high jump (principles vs. pictures) - Thomas, S. (Techniques Magazine, 2023)
There are two events in Athletics (track & field for people who know the sport by its venues name) that are Hinge Moment Principle events. The "High Jump," which is not a jump in how we think of jumping and the "Javelin Throw," which is not a throw. The Hinge Moment Principle is the reason that the High Jump shoe and the Javelin boot have the same spike plate. The four spikes on the heel are there for stopping. The Hinge Moment Principle states that when a body is in linear motion and on end of the body is stopped, the other end continues to move, rotating about the axis formed at the stopped end. The high jump is simply converting horizontal speed into vertical velocity using the Hinge Moment Principle. To cinvert horizontal speed into vertical velocity requires a stopping of the lower body allowing the center of mass to rotate over the take-off leg to create vertical velocity. To convert horizontal speed into vertical velocity requires the jumper to master technique in three areas: (1.) Approach, (2.) Takeoff and (3.) Bar Clearance. The high jump is on continuous movement and must always be performed as one continuous movement.